Unilateral Congenital Cataracts: Best Practices and Case Studies for Effective Management - Imelda, Eva; Sari, Cut Refida; Toshniwal, Navneet Shamsundar (Indonesian Journal of Case Reports, 2024)
Congenital cataract is a clouding of the eye lens in children, which contributes to blindness in 5% to 20% of children throughout the world. Cataracts can occur unilaterally or bilaterally and can vary in size, morphology, and degree of opacification. This report aims to comprehensively diagnose and treat unilateral cataracts and provide optical rehabilitation. A 3-month-old baby boy was brought by his family with complaints of a white spot on the right eye, which the family had known about since the patient was one month old. The patient was diagnosed with a congenital cataract and underwent surgery, which included aspiration irrigation, primary posterior capsulotomy, and anterior vitrectomy under general anesthesia. The use of glasses is chosen as optical rehabilitation. Collaborative management is also done with pediatric specialists, ENT, and pediatric cardiology. It was concluded that congenital cataract management aims to prevent amblyopia by clearing it as soon as possible (Clear Visual Axis) and optical rehabilitation (Clear Retinal Image) to improve the vision prognosis.